Implementasi Pendidikan Multikultural dalam Pembelajaran Bahasa Arab - Annisa Ayunda; Hikmatul Fadilah; Putri Lathifah Zauharo; Sahkholid Nasution (Pusat Riset dan Inovasi Nasional, 2025)
The implementation of multicultural education in Arabic language teaching in Indonesia is very important given the diversity of cultures, ethnicities and religions that exist. This approach aims to build an attitude of tolerance, mutual respect, and adaptability among students. This research uses a qualitative method with a descriptive approach to understand this phenomenon in depth. This approach is carried out by reviewing various relevant literature. The analysis process begins with data reduction, which is the selection and simplification of important information from sources that have been collected through the process of reading and analyzing a number of sources, such as scientific journals, books, articles, websites, and other supporting documents. Furthermore, the data is presented in narrative form to describe the phenomenon as a whole. The results show that multicultural education supports students' character development and enriches the learning experience through the introduction of Arabic and local cultures. Effective implementation strategies include the integration of multicultural content in the curriculum, the use of varied learning methods, teacher training, and the utilization of technology. However, challenges such as value conflicts, stereotypes and socio-economic disparities need to be addressed with inclusive solutions. Thus, multicultural education in Arabic language teaching is expected to create students who are not only competent in the language but also globally minded and able to contribute to a harmonious and tolerant society.